Does neighbourhood unemployment affect the springboard effect of low pay? - Plum, Alexander; Knies, Gundi (Colchester, 2015)
"There is considerable debate on whether the employment and earnings prospects are better for those on low pay or for the unemployed. We use Understanding Society data for England and estimate dynamic random effects panel models which show robust evidence that the future unemployment risk is lower for those who are currently on low pay compared to those who are currently unemployed and the low-paid also have a higher chance than the unemployed of becoming higher-paid. These findings are most marked in neighbourhoods with high unemployment which is attributable to the much poorer prospects of the unemployed in these neighbourhoods."